Dynamics of Gender-Specific Behaviors in the Digital Educational Environment - Badjanova, Jeļena; Iliško, Dzintra; Ignatjeva, Svetlana; Nesterova, Margarita (International Journal of Interactive Mobile Technologies (iJIM), 2021)
During the social distancing, an increasing number of people use communication applications, various types of digital tools and programs. Various video conferencing platforms are regularly used in the educational environment. The study presents the analyses how intensive is the use of Information and Communication Technologies (ICT) in the educational environment and how it can change cognitive-behavioral gender differences. This is particularly important to pay a special attention to the analysis of gender as a dynamic category, to take into account the processes of gender socialization and transformation of gender identification in the changing social environment. The research methods also included a set of additional methods, such as a focus group on different aspects of gender-specific behavior in the digital learning environment, putting together collages, as well as the method of the unfinished sentence related to the impact of ICT on teachers' professional development and well-being. In the course of the study, it was recognised that the design of social models of male and female gender-specific behaviour includes more than the basic gender identity and gender stability: in today's society, there is a multiplicity of views on the similarities and differences of gender-specific behaviours, and a rapid change in the accepted social guidelines and behavioural patterns is in progress, socio-cultural norms that define the psychological characteristics of women and men, their patterns of behaviour.